Capacity of community health centers to treat snakebite envenoming in indigenous territories of the Brazilian Amazon - Sachett, André (2024)
Introduction: The deaths from and morbidities associated with snakebites - amputations, loss of function in the limb, visible scarring or tissue damage - have a vast economic, social, and psychological impact on indigenous communities in the Brazilian Amazon, especially children, and represent a real and pressing health crisis in this population. Snakebite clinical and research experts have therefore proposed expanding antivenom access from only hospitals to include the community health centers (CHC) located near and within indigenous communities. However, there are no studies examining the capacity of CHCs to store, administer, and manage antivenom treatment. In response to this gap, the research team calling for antivenom decentralization developed and validated an expert-based checklist outlining the minimum requirements for a CHC to provide antivenom. Methods: The objective of this study was thus to survey a sample of CHCs in indigenous territories and evaluate their capacity to provide antivenom treatment according to this accredited checklist. The checklist was administered to nurses and doctors from 16 CHCs, two per indigenous district in Amazonas/Roraima states. Results: Our results can be conceptualized into three central findings: 1) most CHCs have the capacity to provide antivenom treatment, 2) challenges to capacity are human resources and specialized items, and 3) antivenom decentralization is feasible and appropriate in indigenous communities. Conclusion: Decentralization would provide culturally and contextually appropriate care accessibility to a historically marginalized and underserved population of the Brazilian Amazon. Future studies should examine optimal resource allocation in indigenous territories and develop an implementation strategy in partnership with indigenous leaders. Beyond the indigenous population, the checklist utilized could be applied to community health centers treating the general population and/or adapted to other low-resource settings.